PENGARUH SUASANA TOKO DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN (Studi Kasus pada Pelanggan ICOS Cafe) - Krisjayanti, Monika; DS, Agus Hermani (Jurnal Ilmu Administrasi Bisnis, 2018)
In this day and age, the culinary industry has grown rapidly, especially cafes. Culinary competition is so tight that culinary entrepreneurs begin to pay attention to the wants and needs of customers or consumers. ICOS Café as one of the culinary industry there are still customers who are not loyal. This is due to the growing number of competing cafes that have sprung up and can provide a more attractive shop atmosphere and better service quality so customers turn to competitor cafes. This study aims to determine how the influence provided by the store atmosphere and quality of service to customer loyalty ICOS Café. Type of sampling using purposive sampling. Type of research used is explanatory research while the data collection techniques using questionnaires and interviews. The number of samples used in this study as many as 100 respondents consists of all customers ICOS Café. The results of this study indicate that store atmosphere and service quality variables each have a significant, strong and positive influence on customer loyalty. Two variables have been tested in stages and together show that the variables of store atmosphere (0.745) and service quality (0.734) simultaneously have a strong relationship to customer loyalty variables. The amount of contribution owned by store atmosphere variables greater than the amount of donation owned by the quality of service, the coefficient of determination (R ²) for store atmosphere variables by 55.5% and service quality of 53.8%. Suggestion that can be submitted in this research is company can increase customer loyality hence company need to improve shop atmosphere to be more modern and instagramable, so as not to lose with cafe competitor and society interested to visit cafe. Cafes are also advised to improve the quality of service related to the accuracy of employees in the calculation of payments, cafes are also advised to increase employee knowledge of ICOS Café products so as to provide optimal service quality to customers.